Conversion of waste seed oil of Citrus aurantium into methyl ester via green and recyclable nanoparticles of zirconium oxide in the context of circular bioeconomy approach. (December 2021) - Rozina,; Ahmad, Mushtaq; Zafar, Muhammad
Highlights: Introduction of Waste seeds of Citrus aurantium as a novel energy crop for Circular Economy. Catalytic application of designed green nano-particles in the conversion mechanism. Synthesis and structural characterization of nano-particles and synthesized methyl ester. Application of innovative analytical techniques for precision & accuracy findings. Abstract: In the current scenario of energy crises and depleting fossil fuels, there is need of sustainable and cheaper interventions with green technology to address these obstinate glitches. Biodiesel produced from waste, non-edible seed oils is a cleaner, green and alternate source of fuel for diesel engines which can possibly add to circular bioeconomy. In this study, Citrus aurantium a novel, nonedible and waste seed oil (38% w/w) producing feedstock was subjected to biodiesel synthesis using recyclable zirconium oxide nano particles synthesized with Alternanthera pungens aqueous leave extract. Maximum yield of 94% was obtained through optimized reaction parameters of methanol to oil molar ratio 6:1, reaction time 120 min, temperature 87.5 °C and catalyst loading of 0.5 wt% using Response Surface Methodology. Green nano particles of zirconium oxide were characterized via Scanning Electron Microscopy (SEM), X-Ray Diffraction (XRD) and Energy diffraction X-Ray (EDX) while; physiochemical characterization of synthesized biodiesel was carried through Fourier-transform infrared spectroscopy (FTIR), Gas Chromatography/Mass spectroscopy (GC/MS), and Nuclear magnetic resonance (NMR 1 H and 13 C). Fuel properties of methyl ester met international standards of ASTM D-6571, EN 14214 and China GB/T 20828-2007. It was concluded that biodiesel production from Citrus aurantium waste and non-edible seed oil can be efficiently employed for generation of renewable energy which would further provide assistance in transformation of linear economy to circular bioeconomy.